2008
DOI: 10.1016/j.eurpsy.2008.01.851
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant brain stem function in schizophrenia

Abstract: Background and Aims:Earlier research has shown that schizophrenic individuals process complex sound in aberrant ways (Olsson.O., Dissertation, Lund, 2000). It has also been shown that they abnormally perceive forward and backward masking (Källstrand et al., Psychiatry Res. 2002 Dec 15; 11 (1-2); 115-25). Experiments described in those studies indicate that in schizophrenia, brain-stem activity is involved, where primitive sorting of sound elements takes place. Brain Stem Response Audiometry (BSRA) shows that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some studies have suggested that when these patient groups have been examined with brainstem audiometry, the resulting brainstem audiograms have displayed illness-specific aberrations [9,14,17,21]. These aberrations have also been noted in unpublished observations.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies have suggested that when these patient groups have been examined with brainstem audiometry, the resulting brainstem audiograms have displayed illness-specific aberrations [9,14,17,21]. These aberrations have also been noted in unpublished observations.…”
Section: Introductionmentioning
confidence: 97%
“…Prior studies have suggested that patients suffering from schizophrenia and ADHD may process certain sound stimuli in the brainstem in an unusual or aberrant manner [ 3 - 20 ]. Some studies have suggested that when these patient groups have been examined with brainstem audiometry, the resulting brainstem audiograms have displayed illness-specific aberrations [ 9 , 14 , 17 , 21 ]. These aberrations have also been noted in unpublished observations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on research indicating that specific ABR peaks are correlated with certain psychiatric symptoms, it has been speculated that ABR could be used as a complementary clinical tool to aid in the diagnosis of schizophrenia, 10,14 bipolar disorders, 12 autism spectrum disorders, [15][16][17] and ADHD. 11,18,19 Methylphenidate (MPH) is a psychostimulant commonly prescribed as a first-line therapy for pediatric ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…21 Previous studies by this group have shown that schizophrenic patients perceive sounds differently than nonschizophrenic comparison subjects, possibly partly reflecting abnormal functioning of the lower portion of the auditory pathway. 22,23 More specifically, auditory masking has been shown to be aberrant for schizophrenic patients. 22 Auditory forward masking refers to the reduced ability to detect a stimulus when preceded by a masking sound.…”
Section: Introductionmentioning
confidence: 99%